VD_FINDINFO Jug / 2021 / 304 vom 2. März 2021 - VD Tribunal cantonal (2021)
VIOL, FIXATION DE LA PEINE, EXPULSIONDROIT PÉNAL, TORT MORAL | 190 al. 1 CP, 47 CP, 66a al. 1 let. h CP, 66b CP, 10 al. 3 CPP (CH), 398 al. 3 let. b CPP (CH)